1990
DOI: 10.1159/000216114
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin at Very Ultra Low Dosage in Healthy Volunteers: Effects on Bleeding Time, Platelet Aggregation and Coagulation

Abstract: Aspirin at very ultra low dosage was tested in healthy volunteers (n = 20) in a randomized, double-blind and placebo-controlled trial. The results showed a bleeding time reduction (p < 0.05) in volunteers having previously ingested aspirin. Platelet aggregation on platelet-rich plasma was not statistically modified after aspirin ingestion. Thrombin clotting time was always higher (p < 0.05) in the treated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Although NO plays an important role in modifying platelet adhesion in portal hypertension [2] , PGI2, a powerful vasodilator prostanoid with antithrombotic properties, was also found increased in mesenteric vascular bed [3] . Ultra low dose aspirin (ULDA) has shown prothrombotic activity when analysed in humans and in the interface platelet-endothelial cell [4,5] . Previous papers have shown the potentially beneficial effect of ULDA in portal hypertensive animals normalizing altered platelet activity and induced hemorrhagic time [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Although NO plays an important role in modifying platelet adhesion in portal hypertension [2] , PGI2, a powerful vasodilator prostanoid with antithrombotic properties, was also found increased in mesenteric vascular bed [3] . Ultra low dose aspirin (ULDA) has shown prothrombotic activity when analysed in humans and in the interface platelet-endothelial cell [4,5] . Previous papers have shown the potentially beneficial effect of ULDA in portal hypertensive animals normalizing altered platelet activity and induced hemorrhagic time [6] .…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports that investigate platelet aggregation in vivo in portal hypertension, and none of them utilize a prehepatic portal hypertension model. Aspirin (ASA) in ultra-low doses (ULD) was reported as a potent enhancer of platelet aggregation in several reports [4][5][6][7] , in experimental and clinical research studies. The aim of this study was to evaluate in vivo the changes in platelet aggregation in a model of portal hypertension in the absence of liver damage and the modifi cations observed after administering ASA in ULD.…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the fact that aspirin is a relatively weak antiplatelet agent. However it has been suggested that some patients are resistant to the antiplatelet effects of aspirin [25]. The term aspirin nonresponder has been used to describe those patients who show a reduced response to aspirin as measured by platelet function assays.…”
Section: Aspirinmentioning
confidence: 99%